Sistem informasi potensi desa berbasis web untuk pemberdayaan masyarakat di Kabupaten Banyuwangi - Munazilin, Akhlis; Udmah, Lailatul (Universitas Merdeka Malang, 2024)
The potential that exists in each village has its own attraction for local residents. The potential of a village can make it easier for its residents and even other people to see or know about the advantages that exist in the village. In the digital era, almost all types of work use information systems to facilitate the service process, one of which is service to the community. Villages have an obligation to provide good services to the community. The aim of this research is to develop a village potential website to make it easier for residents or communities who want to access village potential information. The information system development method used is the waterfall method with the PHP programming language. Supporting software used includes Power Designer, localhost XAMPP server, and MySQL database. The research results show that the village potential information system created is very useful in helping to increase insight and empower local communities. Local people and the general public can easily access information via the website. With an application that can facilitate access to information quickly, precisely and accurately, it is hoped that it can provide more optimal services for village communities.